Pengaruh Persepsi Konsumen, Gaya Hidup, Terhadap Perilaku Konsumen Dalam Pembelian Produk Second Pada Toko Pakaian Bekas Cowboy Collection Di Air Tawar Padang Di Era Pandemic Covid-19 - Muhammad Ricard Alzikri; Febsri Susanti (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to examine and analyze the effect of consumer perceptions and lifestyle on consumer behavior in purchasing second-hand products (a case study of consumers at a used clothing store, Cowboy Collection, Padang). This type of research is quantitative research with multiple linear regression data analysis. The sample of this research is consumers at the cowboy collection used clothing store Padang. Samples were taken by non-probability sampling technique. The number of respondents 98 people. Data was collected using a questionnaire. The variables in this study are the independent variables, namely consumer perceptions (X₁) and lifestyle (X₂) and the dependent variable (Y), namely consumer behavior. From the calculation of the t test, it can be seen that for consumer perception (X₁) the large t-count value of t-table is 4.590 > 0.677 and a significant value is 0.012 <0.05, so the conclusion is that the hypothesis can be accepted or proven true for the consumer perception variable (X₁). So it can be stated that there is a positive and significant influence between consumer perceptions and consumer behavior. While the t test for lifestyle (X₂) the value of t count is large from t table 6.498 > 0.677 and a significant value is 0.000 <0.05 , so the conclusion is that the hypothesis is also accepted for the product quality variable (X₂). So it can be stated that there is a positive and significant influence between lifestyle and consumer behavior. Companies can pay more attention to things that can influence consumer behavior in purchasing products.